South Pole (SPICECORE) 15N, 18O, O2/N2 and Ar/N2 - Severinghaus, Jeffrey P. (IEDA: US Antarctic Program Data Center, 2019)
This data set includes major atmospheric gas and gas isotope data from the SPICECORE project, which recovered a 1750-m ice core at the South Pole in 2015. 15N, 18O of O2, O2/N2, and Ar/N2 are included.